2020
DOI: 10.1111/jgs.16275
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Head Injuries Associated With Antipsychotic Use Among Persons With Alzheimer's disease

Abstract: BACKGROUND/OBJECTIVES Antipsychotic use is associated with risk of falls among older persons, but we are not aware of previous studies investigating risk of head injuries. We studied the association of antipsychotic use and risk of head injuries among community dwellers with Alzheimer's disease (AD). DESIGN Nationwide register‐based cohort study. SETTING Medication Use and Alzheimer's Disease (MEDALZ) cohort, Finland. PARTICIPANTS The MEDALZ cohort includes Finnish community dwellers who received clinically ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…During recent decades, the sequential events that occur in the development and pathology of AD have been extensively studied, yet the precise etiology of the disease remains elusive, and current preventative and curative strategies are largely unsuccessful (Rong et al, 2017;Rasmussen and Langerman, 2019). Considering the complexity of AD pathology, it is apparent that other risk factors also exist besides those known, such as gender, education, smoking, dietary habit, depression, hypertension, diabetes mellitus, obesity, and head injury (Shinohara et al, 2014;Dursun et al, 2016;Badea et al, 2019;Jackson et al, 2019;Tapiainen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During recent decades, the sequential events that occur in the development and pathology of AD have been extensively studied, yet the precise etiology of the disease remains elusive, and current preventative and curative strategies are largely unsuccessful (Rong et al, 2017;Rasmussen and Langerman, 2019). Considering the complexity of AD pathology, it is apparent that other risk factors also exist besides those known, such as gender, education, smoking, dietary habit, depression, hypertension, diabetes mellitus, obesity, and head injury (Shinohara et al, 2014;Dursun et al, 2016;Badea et al, 2019;Jackson et al, 2019;Tapiainen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This wide-spread use of quetiapine might be problematic as safety is not thoroughly evaluated with the use of quetiapine in low dose. However, prior observational studies have indicated increased risk of metabolic disturbances (Carr et al ., 2016), fall-related injuries (Tapiainen et al ., 2020), stroke (Correll et al ., 2015) and all-cause mortality (Gerhard et al ., 2020; Reutfors et al ., 2020) with the use of quetiapine in individuals without severe mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The Kuopio Research Centre of Geriatric Care focuses on pharmacoepidemiology in people with Alzheimer's disease and Parkinson's disease. This includes aetiological research, drug utilization studies and outcome studies [40,41]. Primary sources of data are the nationwide MEDication use and ALZheimer's disease (MEDALZ) study [42] on people with Alzheimer's disease, and the Finnish Medication and Parkinson's disease (FINPARK) study on people with Parkinson's disease [43].…”
Section: University Of Eastern Finland Finlandmentioning
confidence: 99%